(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
Diet, feeding habits, and behavioral activities of Rhesus macaque (Macaca Mulatta) were studied at Charmuguria of Madaripur district from March 2021 to December 2021. Among the five troops, one troop with four age-sex individuals was selected for data collection. Scan sampling methods at 10-minute intervals were used for data collection. Rhesus macaque spent 72% of feeding time on natural foods and 28% on provisioned foods. During the study period, 11 types of provisioned foods were recorded as a diet of Rhesus macaque, of which 73% were unprocessed food, and 27% were processed food. Rhesus macaque depended on various types of provisioned foods like bananas, peanuts, bread, vegetables, guava, chips, and pet foods. A total of 24 plant species belonging to 20 families were identified, which provided food for the studied group. Among the recorded plant families, the Fabaceae family provided the highest portion of the macaque’s diet during the study period. Among the natural food items, 34% were fruits, followed by 27% of leaves, 12% animal matter, grasses (7%), flowers (6%), seeds (4.5%), grains (3%), buds & shoot (2.5%), drinking water (2%), plant roots (1.5%) and soil (0.5%). The Rhesus macaques spent the highest time in resting (37.5%), followed by feeding (25.5%), moving (20.4%), grooming (8.5%), then playing (3.6%), while submission and aggression had 3% and 1.5 % respectively. These days, people are destroying macaque habitats and their feeding plants, so they can’t move freely and don’t get sufficient food. Therefore, the government should take practical steps to conserve Rhesus macaque. Jagannath University Journal of Life and Earth Sciences, 9(2): 147-162, 2023 (December)